THE INFLUENCE OF ADMINISTERING MENIRAN EXTRACT FOR SEVEN DAYS ON BROILERS BEFORE NEWCASTLE DISEASE VACCINATION - I Made Indra Palaguna; Ida Bagus Kade Suardana; Gusti Ayu Yuniati Kencana (Buletin Veteriner Udayana, 2024)
Newcastle disease (ND) is a detrimental viral disease that affects broiler chickens. Chickens that contract the virus post-vaccination cause significant losses for farmers. Administering meniran extract is one alternative that can enhance the effectiveness of vaccination in chickens. This study aims to determine the effect of administering meniran extract for 7 days before vaccination on the antibody titer against Newcastle disease. The research subjects used were 30 broiler DOCs (Day-Old Chicks) aged 1 day to 30 days. The research design employed a Completely Randomized Design with 3 treatments. The research procedures included preparation of the cages, animal treatment, vaccination, blood sampling, and ND antibody titer testing. Data analysis was performed using ANOVA and Regression Analysis. The study showed an increase in the average antibody titer in each treatment group. The results of this study indicate that administering meniran extract can increase the antibody titer in chickens vaccinated with the LaSota (active) vaccine in the first week before vaccination, as seen in the average antibody titer value of the treatment group, which increased up to 4.5 HI units log 2. Based on the results of the study, further research is needed with a longer administration period of meniran extract or different doses to observe the increase in antibody titer.